2017
DOI: 10.1111/jcal.12200
|View full text |Cite
|
Sign up to set email alerts
|

Diverse delivery methods and strong psychological benefits: A review of online formative assessment

Abstract: This article is a review of literature on online formative assessment (OFA). It includes a narrative summary that synthesizes the research on the diverse delivery methods of OFA, as well as the empirical literature regarding the strong psychological benefits and limitations. Online formative assessment can be delivered using many traditional assessment methods. These assessments can be delivered using a variety of programs and software. The benefits of using OFAs include both gains in achievement scores and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 57 publications
3
44
0
3
Order By: Relevance
“…Additionally, the study indicated that formative assessment promotes the development of complex cognitive processes like self-regulation. The study concluded that formative feedback has the potential to encourage student engagement, bolster student enthusiasm to learn, and lead to improved academic achievement (McLaughlin & Yan, 2017). This study adds knowledge to past research by focusing on student perceptions of CMAs, PAAs, and teacher-marked assignments (TMAs).…”
Section: Review Of Literaturementioning
confidence: 73%
See 1 more Smart Citation
“…Additionally, the study indicated that formative assessment promotes the development of complex cognitive processes like self-regulation. The study concluded that formative feedback has the potential to encourage student engagement, bolster student enthusiasm to learn, and lead to improved academic achievement (McLaughlin & Yan, 2017). This study adds knowledge to past research by focusing on student perceptions of CMAs, PAAs, and teacher-marked assignments (TMAs).…”
Section: Review Of Literaturementioning
confidence: 73%
“…Results obtained from one study revealed that instructors can use asynchronous online discussions to assess students' self-regulatory activities, autonomy, communities of inquiry, and writing skills (Vonderwell et al, 2007). In another more recent study, findings suggested that online formative assessment is associated with gains in students' achievement scores (McLaughlin & Yan, 2017). Additionally, the study indicated that formative assessment promotes the development of complex cognitive processes like self-regulation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Results obtained from one study revealed that instructors can use asynchronous online discussions to assess students' self-regulatory activities, autonomy, communities of inquiry, and writing skills (Vonderwell et al, 2007). In another more recent study, findings suggested that online formative assessment is associated with gains in students' achievement scores (McLaughlin & Yan, 2017). Additionally, the study indicated that formative assessment promotes the development of complex cognitive processes like self-regulation.…”
Section: Review Of Literaturementioning
confidence: 90%
“…Student work can be "formative", where the instructor provides constructive feedback to the student, or "summative", where feedback to the student consists of only a grade or mark [93]. In [94], the authors note that online formative assessments (OFAs) improve student achievement and learning.…”
Section: Measuring Learning Effectiveness In Online Systemsmentioning
confidence: 99%
“…Online feedback helps students develop self-regulation (management of academic behavior) and results in higher learner satisfaction [94]. In [94], seven principles are noted for good feedback practices including clarifying what constitutes good performance, encouraging dialogue, encouraging positive motivational beliefs and self-esteem, facilitating self-assessment, delivering high quality information to students regarding their learning, providing information to instructors to help shape teaching, and providing information to students that will assist them in achieving their desired performance.…”
Section: Measuring Learning Effectiveness In Online Systemsmentioning
confidence: 99%